Computed Tomography Chest Findings in COVID-19 Patients - Tamang, Ongden Yonjen; Paudel, Sharma; Kayastha, Prakash; Maharjan, Santosh; Adhikari, Govinda; Upadhyaya, Rudra Prasad; Dawadi, Kapil; Pradhan, Prajina; Rehman, Tanveer; Malla, Saurav Krishna (Journal of Nepal Health Research Council, 2023)
Background:COVID-19 which has caused significant morbidity and mortality around the world has been declared by the World Health Organization to be a global health emergency. Our objective was to find out the lung parenchymal patterns commonly evident in high resolution Computed Tomography in patients with COVID-19 pneumonia. Methods: A retrospective cross-sectional study was conducted at a tertiary multi-specialty hospital in Kathmandu, Nepal. With ethical clearance from the institutional review board, a total of 235 patients with positive reverse transcriptase polymerase chain reaction for COVID-19 and having respiratory symptoms were included in the study. High Resolution Computed Tomography images of chest were retrieved from picture archiving and communication systems retrospectively and studied for the findings commonly attributed to COVID-19 pneumonia. The data was then analyzed using Stata version 14 (Stata Corp, College Station, TX, USA). Descriptive statistics were presented as mean and median while chi-square test was used to assess the association between socio-demographic characteristics and CT severity indices. Results: Out of 235 patients, 174 (74.0%) were males and 61(26%) were females with a mean age of 54.8±14.5 years. The most commonly encountered pattern of pulmonary changes was bilateral involvement in 222 (94.5%) patients followed by ground-glass opacities in 218 (92.8%) patients and peripheral predominance of ground-glass opacities in 211 (89.8%) patients. Conclusions: Chest Computed Tomography abnormalities are common in COVID-19 positive patients with respiratory symptoms. These findings can guide in the assessment of the severity of the disease as well as patient management. Keywords: Computed Tomography; COVID-19; ground-glass opacities; reverse transcriptase polymerase chain reaction